Analysis of Factors That Affect Customer Satisfaction Amid the Covid-19 Pandemic - Endang Brotojoyo; Veronica Titi Purwantini (Common Publisher, 2021)
This research was conducted to determine the effect of price, product quality and service quality on consumer satisfaction at the Katie Jus Jumapolo Restaurant in the middle of the Covid-19 pandemic. The type of research used is quantitative. The population in this study were all consumers of Katie Jus Jumapolo Karanganyar restaurant. With purposive sampling technique, the total sample was 100 respondents. All question items proved to be valid and reliable. The multiple linear regression equation variable Price, Product Quality and Service Quality has a positive effect. The t test results show that the price and product quality variables have a significant effect, while Service Quality has no significant effect on Customer Satisfaction. Simultaneously, all independent variables namely price, product quality and service quality have a significant effect on the dependent variable, namely consumer satisfaction. Based on the results of the calculation of the coefficient of determination (R2), it is known that variations in the variable of customer satisfaction can be explained by the variable price, product quality and service quality to customer satisfaction (Y) = 52.6% while the remaining 47.4% is another variable.